1985
DOI: 10.1113/jphysiol.1985.sp015845
|View full text |Cite
|
Sign up to set email alerts
|

The detection of monosynaptic connexions from inspiratory bulbospinal neurones to inspiratory motoneurones in the cat.

Abstract: SUMMARY1. Simultaneous recordings were made of the discharges of inspiratory bulbospinal neurones and phrenic or external intercostal z-motoneurones in the anaesthetized cat.The connexions between these neurones were studied by the construction of cross-correlation histograms from their discharges.2. Peaks observed in the cross-correlation histograms were divided into three groups on the basis of their time courses: narrow, medium-width and high-frequency oscillations (h.f.o.). Narrow peaks were defined as hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
122
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 49 publications
12
122
0
Order By: Relevance
“…The biphasic feature represents 'motoneurone' action potentials. The presence of an offset positive feature in the rectified but not the unrectified signal suggested that the trigger neurone was (1) a premotor neurone that projected to the monitored motoneurone pool, or (2) a neurone that was tightly synchronized with premotor neurones by functionally antecedent shared inputs (Davies et al 1985;Botteron & Cheney, 1989;Maier et al 1998;Perlmutter et al 1998). The presence of an offset trough in a rectified average was consistent with functional inhibition, i.e.…”
Section: Spike Train Analysis Methods For Each Single Neuronementioning
confidence: 91%
See 2 more Smart Citations
“…The biphasic feature represents 'motoneurone' action potentials. The presence of an offset positive feature in the rectified but not the unrectified signal suggested that the trigger neurone was (1) a premotor neurone that projected to the monitored motoneurone pool, or (2) a neurone that was tightly synchronized with premotor neurones by functionally antecedent shared inputs (Davies et al 1985;Botteron & Cheney, 1989;Maier et al 1998;Perlmutter et al 1998). The presence of an offset trough in a rectified average was consistent with functional inhibition, i.e.…”
Section: Spike Train Analysis Methods For Each Single Neuronementioning
confidence: 91%
“…The evidence for neuronal interactions is based upon measured time-locked fluctuations in the recruitment and firing rates of motoneurones due to direct, indirect or parallel paths. Advantages and limitations of these methods have been considered elsewhere (Cohen et al 1974;Davies et al 1985;Botteron & Cheney, 1989;Maier et al 1998;Perlmutter et al 1998). An additional limitation to feature interpretation had to be considered in this study.…”
Section: Evidence For Functional Associations Of Premotor Neuronesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the ventrolateral n.t.s. has been found in cats, to be essential in both reflex and central control of the respiratory rhythm (Von Euler, Hayward, Martilla & Wyman, 1973;Cohen, 1979;Richter, 1982; Morin-Surun, Champagnat, Boudinot & Denavit-Saubie, 1984;Davies, Kirkwood & Sears, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Three types of synchronization-short-term, broad-peak, and high-frequency oscillation were found in the cross-correlograms between the efferent spikes [43,45]. Crosscorrelograms between spikes of inspiratory bulbospinal neurons and phrenic or external intercostal motoneurons revealed peaks which could be divided into three groups on the basis of the time course: narrow, medium-width, and high-frequency oscillation [19,20]. Intercostal muscle activity during purring of the cat was also analyzed [44].…”
Section: Cross-correlation Analysis Used In Neurophysiologymentioning
confidence: 99%